TRANSDUCERS 2007 - 2007 International Solid-State Sensors, Actuators and Microsystems Conference 2007
DOI: 10.1109/sensor.2007.4300401
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Flexible Parylene-Based Multielectrode Arrays for Retinal and Spinal Cord Stimulation

Abstract: Novel flexible parylene-based high-density electrode arrays have been developed for functional electrical stimulation in retinal and spinal cord applications. These electrode arrays are microfabricated according to single-metal-layer and, most recently, dual-metal-layer processes. A new heat-molding process has been implemented to conform electrode arrays to approximate the curvature of canine retinas, and chronic implantation studies have been undertaken to study the mechanical effects of parylene-based prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…The effect of bending stress on thin-film devices can be assessed by wrapping films around cylinders of specific diameters ranging from hundreds of microns to several millimeters and then either measuring the resistance across the traces or the testing the performance (Ai et al, 2008;Chen et al, 2010;Kim et al, 2010;Lacour et al, 2010;Ochoa et al, 2013). Alternatively, films can be wrapped around spheres (Ochoa et al, 2013;Rodger et al, 2007) and inflatable balloons (Kim et al, 2011). Some devices are self-curling and were shown to maintain function while being bent 90° (Takeuchi et al, 2004) or down to a radius of 2 mm or less (Johnson and Wise, 2012;Yamagiwa et al, 2013).…”
Section: Minimum Bending Diameter Device Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of bending stress on thin-film devices can be assessed by wrapping films around cylinders of specific diameters ranging from hundreds of microns to several millimeters and then either measuring the resistance across the traces or the testing the performance (Ai et al, 2008;Chen et al, 2010;Kim et al, 2010;Lacour et al, 2010;Ochoa et al, 2013). Alternatively, films can be wrapped around spheres (Ochoa et al, 2013;Rodger et al, 2007) and inflatable balloons (Kim et al, 2011). Some devices are self-curling and were shown to maintain function while being bent 90° (Takeuchi et al, 2004) or down to a radius of 2 mm or less (Johnson and Wise, 2012;Yamagiwa et al, 2013).…”
Section: Minimum Bending Diameter Device Designmentioning
confidence: 99%
“…Many different thin-film devices have been demonstrated to be used to stimulate and record from many electrically active tissues such as the spinal cord (Rodger et al, 2007), heart Zhao et al, 2013), muscle (Spence et al, 2007), and cortex Tolstosheeva et al, 2011). Although these studies have demonstrated the performance of the devices for short periods of time for their given application, there have not been comprehensive methods to test the mechanical properties of such thin-film architectures until failure.…”
Section: Failure Of Al2o3 Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the introduction of multielectrodes, investigations began on the effectiveness of multipolar stimulation from one channel [22]. Both bipolar and tripolar configurations have been shown to reduce current spreading, with tripolar achieving the highest degree of selectivity [23][24][25] at the cost of higher power consumption.…”
Section: Frequency Selectivitymentioning
confidence: 99%
“…In 1992, Boppart presented a first flexible electrode and used it to measure evoked potentials in brain slices [66]. The research in this field then followed in more advanced designs by Humayun and Weiland's visual prosthesis team in dual-metallayer processes [67,68]. Recently, another approach for flexible implantable electrode has been presented using ITO/PET (Indium Tin Oxide/PolyEthylene Terephthalate) by ICAS visual prosthesis group [69].…”
Section: Microelectrode Arrays (Meas)mentioning
confidence: 99%